Antibiotic Resistance as a Growing Concern in Pediatric Surgery: A Narrative Review - Kanzode, Sonam; Zafar, Mohammad; Parankar, Shashank; K. Andelkar, Atul (Journal of Neonatal Surgery, 2025)
Antibiotic resistance is a growing challenge in pediatric surgery, significantly impacting clinical outcomes and healthcare systems worldwide. Antibiotics play a critical role in preventing surgical site infections (SSIs), which are particularly dangerous in children due to their underdeveloped immune systems and heightened vulnerability to infections. However, the misuse and overuse of antibiotics have led to the emergence of resistant pathogens, complicating the management of postoperative infections and increasing morbidity, healthcare costs, and the length of hospital stays. This narrative review explores the multifaceted issue of antibiotic resistance in pediatric surgery, examining its contributing factors, clinical implications, and potential mitigation strategies. Key factors driving resistance include the misuse of prophylactic antibiotics, inconsistent adherence to surgical guidelines, and environmental risks within pediatric surgical wards. Resistant pathogens such as Staphylococcus aureus, Klebsiella pneumoniae, and Acinetobacter baumannii have been identified as major contributors to postoperative complications, posing significant treatment challenges. The review highlights the importance of targeted interventions such as antibiotic stewardship programs, adherence to evidence-based surgical protocols, and the integration of innovative technologies like antibiotic-coated sutures and rapid diagnostic tools. Education of healthcare workers and parents is emphasized as a critical strategy to minimize unnecessary antibiotic use. Furthermore, the implementation of strict infection control practices and pediatric-specific guidelines is essential to counteract the rising trend of resistance. Despite advancements in research and infection control, gaps remain in addressing pediatric-specific challenges in antibiotic resistance. Future efforts must focus on multidisciplinary collaboration, enhanced surveillance, and the development of novel therapeutic approaches tailored to pediatric populations. By prioritizing these measures, healthcare systems can safeguard the efficacy of antibiotics and ensure better outcomes for pediatric surgical patients.